Screening of Heat Stress Tolerant in Early Stage of Wheat Seedling using Morphological Parameters - Sharma, Pooja; Singh, Raj; Dahiya, Monika; Kumar, Vikas; Kumar, Amit; Sharma, Anil Kumar (Asian Journal of Biological and Life Sciences)
Wheat (Triticum aestivum) is a Rabi crop and one of the dominant cereal, used worldwide as human staple food and livestock feed. Screening of heat stress tolerance in wheat requires various morphological parameters such as seed weight, seed size, imbibition rate, germination rate, seedling length, shoot length, root structure and its length, chlorophyll content, pH of soil, length of wheat crop. Here we studied six wheat varieties grown in various regions in India. Wheat is normally sown during November and harvested between March and April. For this, here we choose six varieties (DBW71, DBW88, DBW90, HD3059, S0072, and HD2851) of wheat to screen the heat tolerance among the varieties. During the analysis it was observed that DBW71, DBW88 and HD3059 are more heat tolerant than other. Various parameters such as chlorophyll content, shapes of leaves, size of shoots, roots morphology were explored for heat tolerant in wheat.
Keywords: Cereal crop; Germplasm; Heat tolerating and non-heat tolerating; Roots; Seed; Seedling; Stress; Temperature.; Wheat; Wheat (Triticum aestivum)